Prevalence of body fluid exposures and associated risk factors amongst healthcare workers at Avicenne Military Hospital, Morocco - el Kamouni, Youssef; el Bardi, Touria; el Bazi, Kenza; el Amrani, Youssra; el Khannouri, Imane; Meskini, Ali; el Miloudi, Mouhcine; Zouhair, Said; Arsalane, Lamiae (International Journal of Infection Control, 2022)
Objectives: The purpose of this study is to determine the prevalence of body fluid exposures (BFE) and associated risk factors amongst healthcare workers (HCWs), and to evaluate hepatitis B (HBV) vaccination coverage, at Avicenne Military Hospital. Materials and methods: A descriptive and analytical cross-sectional study was conducted over 6 months amongst HCWs at the Avicenne Military Hospital. Data were collected using an anonymous questionnaire. Blood samples were collected from consenting participants, for assaying HBV surface antibodies. Results: One hundred thirty-four HCWs were interviewed, and 86 (64.2%) reported at least one BFE. The median age was 28 (27–34) years, with male gender predominating (54%). Percutaneous exposure was the most common BFE (95%), and the hollow bore needle the most implicated (45%). Only 34% of victims reported their BFE. The multivariate analysis showed that HCWs in a surgical department are 10 times more exposed to BFE (P = 0.003; odds ratio [OR] = 10, 95% confidence interval [CI]: 2–47) compared to HCWs in medical departments (P = 0.009; OR = 0.06, 95% CI: 0.007–0.49) and laboratories (P = 0.04; OR = 0.1, 95% CI: 0.01–0.88). The HBV vaccination rate was 67%. Amongst HCWs tested, 42% were immune to HBV. Immune status between physicians and paramedical staff was significantly different (P = 0.005; OR = 0.2, 95% CI: 0.04–0.55). The immunization rate rose significantly with seniority (P = 0.016; OR = 17, 95% CI: 1.67–169). Conclusion: Our findings highlight the importance of information and continuous training on BFE for HCWs, and the development of strategies to promote and simplify access to the HBV vaccine.